Pengaruh Fasilitas terhadap Kinerja Guru dalam Pembelajaran Daring pada SMP Swasta Erlangga Pematangsiantar - Marto Silalahi; Vivi Candra; Sisca Sisca; Debi Eka Putri; Julyanthry Julyanthry (Universitas Batanghari Jambi, 2022)
The purpose of the study was to determine the effect of work facilities on teacher performance in online learning at Erlangga Private Junior High School Pematangsiantar. This research uses quantitative descriptive analysis method and documentation method. The data analysis technique started from normality test, simple linear analysis, correlation coefficient and determination and hypothesis testing with the help of the IBM SPSS Version 21 program. The results of the simple linear regression analysis showed that there was a positive influence of facilities on teacher performance. The results of the correlation coefficient analysis show that there is a strong and positive relationship between facilities and teacher performance. The results of the partial test with the t test H0 were rejected, meaning that there was a positive and significant influence between the facilities on the teacher's performance.